Plants used to treat malaria in Nyakayojo sub-county, western Uganda - Stangeland, Torunn; Alele, Paul E.; Katuura, Esther; Lye, Kåre A. (Journal of Ethnopharmacology, 2011)
Aim of study: We performed an ethnobotanical study of plants used to treat malaria in Nyakayojo subcounty in south western Uganda because malaria in this region, and in Uganda at large, is still the single most important reason for ill health and mortality. Two of the most vulnerable groups affected by malaria are young children and pregnant women and plants are commonly used in their treatment. Materials and methods: Twenty-eight traditional birth attendants were interviewed about how they used plants to treat malaria. Review of the literature available on all species identified was undertaken. Results: Altogether 56 plant species were used by the informants, 48 of which have been identified to species level. Thirty-two (67%) of the species used by the respondents are documented for antimalarial use in other studies, and nearly half (44%) have documented anti-plasmodial activity. Fifty-five percent of the species were used by 2 or more of the respondents. The most commonly used species were Vernonia amygdalina, the indigenous Aloe species, Justicia betonica, Vernonia adoensis and Tithonia diversifolia. It was common to use more than one plant in a recipe (43%). The respondents had good knowledge of the symptom of malaria, and fairly good understanding of the causes. Conclusion: The interviews show that the group of traditional birth attendants has an extensive and diverse knowledge on plants used in the treatment of malaria. The literature survey may indicate a possible explanation for the use of several plants
Keywords: Antimalarial; Traditional birth attendants; Traditional medicine; Uganda